Bianchi Type-I Bulk Viscosity with a DE Cosmological Model - Daba Meshesha Gusu (Advances in High Energy Physics)
The finding article presents Bianchi type-I universe in the presence of bulk viscous and DE fluid nature of a cosmological model. The solutions of field equations were obtained by assuming hybrid expansion law. The physical significance of the obtained findings illustrates the dominance of bulk viscosity in early and dominance of dark energy fluid emergences in late. This leads to indicate the presence of bulk viscosity nature more effective in early time rather than late times, and also, it shows the dominance of dark energy in late times which grants the current observational result of the universe. Certain physical and geometrical properties of the model are also discussed.